Declarative Models for Business Processes and UI Generation using OCL - Brüning, Jens; Wolff, Andreas (Electronic Communications of the EASST, 2010)
This paper presents an approach to model business processes and associated user interfaces in a declarative way, relying on constraints. An UML-based meta-model to define processes, activities and user-interface objects is proposed. Connecting activities and user interface objects in an integrated model allows expressing interdependencies and mutual effects. Flexible execution logic for workflows and UI control flows are specified by OCL invariants. The model is constructed for the UML tool USE. Using object snapshots, USE can animate and validate business scenarios. Snapshots represent states of a process and a UI at specific times. Such animation enables business process and UI designers to discuss sensible scenarios on basis of the flexible declarative models. The intention is to create validated concrete process models in connection with UI elements that will provide a basis for the system implementation.